CT Evaluation of Unilateral Destroyed Lung among Bangladeshi Population - Hossain, ASM Zakir; Rahman, Md Hafizur (TAJ: Journal of Teachers Association, 2021)
The unilateral destroyed lung is an important cause of morbidity and mortality. The commonest cause of destroyed lung is total post tuberculous sequelae. Primary lung tumors, mediastinal masses, vascular abnormalities, and some others are considered to be other causes of lung destruction. A study was undertaken at the National Institute of Diseases of the Chest and Hospital (NIDCH) on 600 cases from January 2016 to December 2020 to evaluate the etiopathogenesis of unilateral lung destruction and to evaluate hilar structures & the nature and extent of parenchymal damage. The study was performed on 600 patients with unilateral lung destruction, of whom 416(69.33%) had left lung destruction. Pulmonary tuberculosis was found to be the cause in 504(84%) patients. All patients had an X-ray chest and CT scan of the chest (contrast CT/ HRCT). However, 96(16%) non-tuberculous patients had their main bronchi occluded with extraluminal compression or by the intraluminal lesion. TAJ 2021; 34: No-1: 75-79